2006
DOI: 10.1016/j.jmaa.2005.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a model for the dynamics of prions II

Abstract: A new mathematical model for the dynamics of prion proliferation involving an ordinary differential equation coupled with a partial integro-differential equation is analyzed, continuing the work in [J. Prüss, L. Pujo-Menjouet, G.F. Webb, R. Zacher, Analysis of a model for the dynamics of prions, Discrete Contin. Dyn. Syst. 6 (2006) 225-235]. We show the well-posedness of this problem in its natural phase space Z + := R + × L + 1 ((x 0 , ∞); x dx), i.e., there is a unique global semiflow on Z + associated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 9 publications
1
87
0
Order By: Relevance
“…On the one hand, part (b) of Theorem 1.2 guarantees uniqueness of monomer-preserving weak solutions in the natural state space L 1 (Y, ydy) and includes as a particular case the uniqueness result obtained in [3] for constant rates τ , β, µ and k 0 ≡ 1. Our proof is however completely different and does not rely on the special structure of (1)- (2) in that case.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the one hand, part (b) of Theorem 1.2 guarantees uniqueness of monomer-preserving weak solutions in the natural state space L 1 (Y, ydy) and includes as a particular case the uniqueness result obtained in [3] for constant rates τ , β, µ and k 0 ≡ 1. Our proof is however completely different and does not rely on the special structure of (1)- (2) in that case.…”
Section: Introductionmentioning
confidence: 86%
“…Some of the results have subsequently been improved in [8]. The pde problem corresponding to (10), (11) has been studied in [3], where well-posedness of certain mild solutions and global asymptotic stability of the steady states are shown. Results for the original equations (1)-(4) not imposing data of the form (10), (11) can be found in [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Prüss and colleagues [45] demonstrated that the prion phenotypes were globally asymptotically stable and not merely locally stable, through deriving a Lyapunov function. Engler et al [46] analyzed the well-posedness of the generalization of the NPM where aggregate sizes were continuous, instead of discrete. As such, rather than an infinite system of ordinary differential equations, the system consisted of a single ODE for protein in the normal configuration and a PDE specifying the distribution of aggregate sizes.…”
Section: Establishing a Mathematical Framework Of Prion Aggregate Dynmentioning
confidence: 99%
“…While this formulation departs from the physically discrete nature of aggregates, in the limit of large aggregate sizes these formalisms are provably equivalent [47] and the use of PDEs permits a wider array of mathematical techniques. Most notably, the continuous relaxation on aggregate sizes has permitted determination of the explicit asymptotic density [44,46] ] prion system [53][54][55], but linking experimental outcomes uniquely to specific kinetic parameters remains challenging.…”
Section: Establishing a Mathematical Framework Of Prion Aggregate Dynmentioning
confidence: 99%
“…In these papers, positivity and the spectral theory of C 0 -semigroups, but also Volterra equations, played an important role. Mathematical biology reappeared several times in Jan's work [33,35,87] and in particular in his important papers [67,71] with G. Webb and others about the longterm behavior of prion models. Moreover, he commonly treated biological systems in his teaching in ODE and dynamical systems, as witnessed in the introductory book Mathematical Models in Biology [B3] (in German).…”
mentioning
confidence: 99%